Imagining Compromised Creativity: Art and Fear in Shostakovich Bio-Fiction. (2nd January 2020) - Schwalm, Helga
ABSTRACT: The life of the composer Dmitri Shostakovich features in several contemporary anglophone bio-fictions, both novels and film, raising the question of the larger implications of Shostakovich's life in art today. In my paper, I aim to address how such Shostakovich bio-fictions reinvent the composer's creative labour in the context of World War II, Stalinist and post-Stalinist politics. Shostakovich's life as artist and man appears torn between fear of persecution, social commitment, and the claim of individual, aesthetic autonomy tied to a controversial degree of political dissent. In Western eyes, the Soviet composer thus epitomizes the transnational figure of the twentieth-century artist – compromised, yet achieving an expression of his personal voice, creating an emphatically modern art that is bound to its times and yet ultimately eludes both the dictates of politics and mimesis.